WORLD ECONOMY AND GLOBAL FINANCIAL SYSTEM (Ustozlar uchun, 2025)
This article examines the structure and dynamics of the world economy and the global financial system. The global economy is shaped by international trade, investment flows, production networks, and technological innovation, while the financial system provides the mechanisms for allocating capital, managing risk, and facilitating economic activity across borders. These systems promote economic growth, development, and global interconnectedness, but they also face challenges such as financial crises, market volatility, inequality, and geopolitical tensions. The study highlights the importance of international cooperation, regulatory frameworks, and technological integration, including digital finance and fintech innovations, to ensure stability, efficiency, and equitable participation in the global economy. By effectively managing these systems, countries can foster sustainable economic growth, strengthen financial resilience, and enhance prosperity worldwide.